Biofilm System Design and Comparative Study of Biomedia using in Domestic Wastewater Treatment - Sharipuddin, Nur Shaza Syahirah; Awang, Zarizi (Progress in Engineering Application and Technology, 2021)
The sewage treatment plant (STP) system is very important because of the need of treatment that must comply with the regulatory standard discharge. Because of the high population people especially in the urban area, the important of the efficient and small footprint of treatment will become choice of the developer. The current conventional domestic sewage treatment required a longer time and more space in treating wastewater pollutants. Since there are huge potential on upgrading an existing plant to cater more capacity of wastewater, these attach growth technology will be the option for the developer to construct or upgrade existing sewage treatment plant with lower cost. Hence, these study focuses to compare with the various types of attach growth system and media in the market. From the study, shows that attach growth system using media namely Cosmo Ball works effectively compared to other type of media, where it is 20% more efficient. It also seems to be the most efficient biomedia when it effectively works on the other factor such arrangement of biomedia and surface properties. This study also shows that biofilm system is the best system in term of performance compliance, plant sizing and maintenance issue.